Distributions of Traces of Frobenius for Smooth Plane Curves Over Finite Fields. Issue 1 (2nd January 2019) - Lercier, Reynald; Ritzenthaler, Christophe; Rovetta, Florent; Sijsling, Jeroen; Smith, Benjamin
ABSTRACT: We analyze the variation around the mean of the distribution of the number of rational points on non-hyperelliptic genus 3 curves over finite fields, by extrapolating from results on the distribution of traces of Frobenius for plane curves whose degree is small with respect to the cardinality of their finite base field. We put our results in perspective with a numerical study for prime fields of characteristic 11 ⩽ p ⩽ 53. Our methods shed some new light on the asymmetry of the distribution around its mean value, which is related to the Serre obstruction.